Shaping the Landscape of Rural Communes in the Aspect of Green Infrastructure Creation - Barbara Żarska; Beata Fornal-Pieniak; Ewa Zaraś-Januszkiewicz (Barometr Regionalny, 2015)
Maintenance of ecological balance and creation of green infrastructure in the landscape are important features of sustainable development. This is strictly connected and correlated with the planning of land use and spatial management. The obligation of green structure creation has a legal basis (the State, European Union and international levels ), EU development and conservation strategies and adaptation planes for climate change such as transition to a green economy. The aim was to present the needs and special approach, called the method of “ecological truss,” to landscape green structure planning in rural areas in central Poland, in Tarłów Commune, creating better possibilities to reconcile nature and biodiversity protection with land use and economic management. Creating rich green infrastructure leads to “ecologization” of the whole area and greater harmony of landscape. It supports strong opportunities and decreases endangerments indicated in documents of local development plans. Rich green infrastructure is a tool to approach closer sustainable development and give a significant chance, especially in peripheral and underdeveloped areas, for better living conditions for local people based on permanent use of natural and cultural values of the landscape rather than degrading them.